Evaluating anticancer activity of plant-mediated synthesized iron oxide nanoparticles using Punica Granatum fruit peel extract - Yusefi, Mostafa; Shameli, Kamyar; Roshafima, R. A.; Pang, Siew Wai *; Teow, Sin Yeang * (Elsevier, 2020)
Magnetic iron oxide nanoparticles (IONPs) are increasingly being studied for potential anticancer application to circumvent off-target cytotoxicity and other side effects from conventional chemotherapy. In this study, four different weight% of Punica granatum fruit peel extract were used as green stabilizers to synthesize IONPs followed by a series of characterization experiments and in vitro anticancer evaluation. Results revealed that all synthesized IONPs have high degree of crystallinity and purity. The optimum saturation magnetization, and hydrodynamic size were found to be ∼69 emu.g−1, and 26.52 nm, respectively. Morphological studies demonstrated that adding peel extract decreased size of NPs with the average particle size below 11 nm. Cytotoxicity assay showed that the IONPs were not reactive (IC50 > 250 μg/ml) against colon (HCT116), breast (MCF7), cervical (HeLa) and lung (A549) cancer cell lines and two normal cell lines derived from human colon and kidney (CCD112 and HEK293). Specifically, IONPs with 2 and 4 wt% of peel extract displayed potent anticancer activities (IC50 of 197.46 and 85.06 μg/ml respectively) against nasopharyngeal carcinoma (NPC) cell line, HONE1. Overall, this study shows the characterization of green synthesized IONPs and its potential use as anticancer therapeutic agents against NPC cells